Optical single-shot readout of spin qubits in silicon - Andreas Gritsch; Alexander Ulanowski; Jakob Pforr; Andreas Reiserer (Nature Communications)
Abstract Small registers of spin qubits in silicon can exhibit hour-long coherence times and exceeded error-correction thresholds. However, their connection to larger quantum processors is an outstanding challenge. To this end, spin qubits with optical interfaces offer key advantages: they can minimize the heat load and give access to modular quantum computing architectures that eliminate cross-talk and offer a large connectivity. Here, we implement such an efficient spin-photon interface based on erbium dopants in a nanophotonic resonator. We demonstrate optical single-shot readout of a spin in silicon whose coherence exceeds the Purcell-enhanced optical lifetime, paving the way for entangling remote spins via photon interference. As erbium dopants can emit coherent photons in the minimal-loss band of optical fibers, and tens of such qubits can be spectrally multiplexed in each resonator, the demonstrated hardware platform offers unique promise for distributed quantum information processing based on scalable, integrated silicon devices.